Analysis Of Relationship Structure And Role Of Actors In Vegetable Farming Social Networks (Case Study Of Vegetable Farmers In Basket Hamlet, Wayame Village, Ambon City) - Fifi hairani sitania; August E Pattiselanno; Paulus Melkianus Puttileihalat (Cita konsultindo, 2023)
This study aims to analyze the relationship and structure of social networks of vegetable farmers. This research was conducted in Basket Hamlet, Wayame Village, Ambon City. Quantitative research approach, saturated sampling in targeting a sample of 20 farmers. Data analysis uses Spearman Rank to see the relationship between variables. The results showed that the social network structure of vegetable farmers based on the issue of each information is generally open network, where the relationship characteristics are loose or low. Actors who play an important role in social networks are P16 from their role as Bdrige or connecting bridges between extension workers and farmers, especially those related to Saprodi information, while information related to marketing and business capital is obtained through actors who play the role of Leason.